Perceval's narrative : a patient's account of his psychosis ; 1830 - 1832 - Perceval, John Thomas, 1803-1876; Bateson, Gregory, 1904-1980 (Stanford, Calif. : Stanford Univiversity Press, 1961)
"Perceval's Narrative was originally published in two volumes, 1838 and 1840, under a different title ... This edition contains all of the first volume and much of the second"